Vulnerability assessment and landslide risk analysis : application to the Loures Municipality, Portugal - Guillard, Clemence (2016)
Tese de doutoramento, Geografia (Geografia Física), Universidade de Lisboa, Instituto de Geografia e Ordenamento do Território, 2016